Pengaruh Transparansi Dan Akuntabilitas Keuangan Terhadap Pengelolaan Keuangan Bumdes Di Kecamatan Pacet - Salsabilla Ayu Wishmilia; Fajar Syaiful Akbar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the effect of transparency and financial accountability on the financial management of BUMDes in Pacet District using quantitative research methods. The sampling technique used a Likert scale to determine measurements and purposive sampling for sampling with a total of 3 respondents in 16 BUMDes, so that a total of 48 respondents. The analysis technique used in this study is the PLS-SEM analysis technique to test the validity and reliability (outer model test) and to test the coefficient of determination (inner model test). Based on the results of the research conducted, it shows that transparency has no significant effect on BUMDes financial management. Financial accountability has a significant effect on BUMDes financial management. Keywords: Transparency, Financial Accountability, Financial Management, BUMDes